Preparation and Characterization of Red Dragon Fruit (Hylocereus polyrhizus) Starch as Solid Medicinal Additive - Alfiona, Melisa Nia; Intan Martha Cahyani; Sari, Wulan Kartika (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2024)
Starch is often used as a filler, crusher, and binder in solid preparations. One source of starch can be found in red dragon fruit stems. When making starch, browning often occurs which causes the flour to become brownish, which can reduce public acceptance. Efforts are made to prevent browning in the starch making process by using sodium bisulfite solution. This study aims to determine the effect of different sodium bisulfite soaking times on the characteristics of red dragon fruit stem starch (Hylocereus polyrhizus) to be used as a solid preparation additive and to determine the length of sodium bisulfite soaking time that can produce red dragon fruit stem starch (Hylocereus polyrhizus) characteristics that meet the standards of solid preparation additives. The results of the analysis showed significant differences in yield, moisture content, flow velocity, angle of repose, pH, solubility, expandability, compressibility index, bulk density, tap density, true density, and Hausner index. FTIR analysis showed that red dragon fruit stem starch contains starch functional groups. Based on the results of the red dragon fruit stem characterization test, the best treatment was obtained, namely 1 hour soaking, producing starch with physical characteristics suitable for solid preparation additives.